Hubungan antara Pengetahuandengan Sikap Siswa SMA Negeri di Kota Banda Aceh terhadap Pemanasan Global - Farrah Fitria; Cut Nurmaliah; Djufri . (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
The objective of this research was to find out the correlation between knowledge and attitude of high school students in Banda Aceh toward global warming. The research was conducted on a class XI student of second semester of the school year 2015/2016 with the sample size 86 students selected by using a random sampling. The data was collected by using questionnaires, interviews and observation. The data was analyzed by using statistical test product moment correlation and to test the hypothesis by using t-test. The results showed that (1) the average knowledge of high school students in Banda Aceh is enough (11.89 or 59.45%), (2) the average attitude of high school students in Banda Aceh is enough (56.93, or 71.16%), (3) knowledge has a high correlation (r = 0.611) with the students attitudes toward global warming. The conclusions of this study showed that (1) knowledge of high school students class XI in Banda Aceh toward global warming is enough, (2) the attitude of high school students class XI in Banda Aceh toward global warming is enough, (3) there is a significant correlation between knowledge and attitude of high school students in Banda Aceh toward global warming.Key words: knowledge, attitude, student, global warming